Microscopic measurement of photon echo formation in groups of individual excitonic transitions. - Langbein, W; Patton, B (2005)
The third-order polarization emitted from groups of individual localized excitonic transitions after pulsed optical excitation is measured. We observe the evolution of the nonlinear response from the case of a free polarization decay for a single transition, to that of a photon echo for many transitions. The echo is shown to arise from the mutual rephasing of the emission from individual transitions.